Visual notes for architects and designers - Crowe, Norman; Laseau, Paul, 1937- (Hoboken, N.J. : Wiley, 2012)
'This show-by-example sourcebook clearly illustrates proven methods and procedures for keeping a highly useful visual notebook. Visual Notes for Architects and Designers demonstrates how to make rapid, notational sketches that serve as visual records for future reference, as well as improve understanding and facilitate the development of ideas. It shows how to expand knowledge of a subject beyond what is gained through observation or verbal representation alone'--
Includes bibliographical references and index.
Keywords: Communication in architectural design; Visual perception